Konstruktivisme dan Inovasi Manajemen Organisasi Pendidikan: Sebuah Kajian Paradigmatik - Heri Iswanto (Alpatih Harapan Semesta, 2026)
This article discusses the concept of constructivism as a foundation for innovation in educational organizational management, particularly in the context of educational institution governance. In an era of rapid global change, innovation in educational management is crucial to ensure the relevance and sustainability of educational institutions. The constructivist approach, which emphasizes active learning, experiential understanding, and individual knowledge construction, can be a paradigm that makes a significant contribution to designing more effective managerial systems and structures. This article uses a qualitative approach with a literature review to explore how constructivism can be applied to educational management innovation. It was found that constructivist principles can strengthen collaborative dynamics, shared knowledge-based decision-making, and the development of more adaptive and responsive managerial models to change. The results of this study indicate that the application of constructivism in educational governance can encourage